Tax “Burden” and International Tax Competition - Gylys, Povilas (Ekonomika, 2006)
The article deals with the interconnected issues of tax “burden” and international tax competition. Author bases his argumentation vis’a vis these issues on holistic assumptions, namely on the postulates that the public sector is part of the economy and that taxes are not simply a burden laid down on the private sector, but the source of investment in the production (procurement) of public goods. Furthermore, author stresses that for more than a century one can follow the tendency of the increasing share of tax revenues in the national product, the so-called as Wagner’s law. In recent decades, another - international-factor of fiscal policy is playing an increasingly importan role. This is tax competition among national states. This factor poses threat to tax bases of sovereign countries and leads, as some assume, to the appearance of tax havens, tax poaching, race-to-the botton, social dumping and other negative phenomenan which distort the natural course of economic development. This trend is supported by power centers which pursue the individualistic economic strategy and base their perception of economy on the premises of methodological individualism Some other power centers, institutions, on the other hand, resist this tendency as harmful to the global welfare. The United Nations, OECD and partly EU assert that international harmonization in the field of taxation could be conductive to economic growth and prosperity of mankind.